2015
DOI: 10.1111/hsc.12294
|View full text |Cite
|
Sign up to set email alerts
|

Information, connection and giving back: peer support outcomes for families following acquired brain injury in South Australia

Abstract: This study aimed to identify the experiences and outcomes of participation in Families4Families Inc., a peer support network for families following acquired brain injury (ABI) in South Australia. Prior to the programme's launch in January 2013, new members of the network were invited to participate in pre- and post-programme phone interviews to identify benefits and limitations of the programme, and identify outcomes of participation. Fifty-five members (20 people with ABI; 35 caregivers) participated in pre-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The need for peer support from other families with direct experience of CCD following TBI was a strong theme to emerge from this study and reinforces positive research findings from peer mentoring programmes (49,50). Relatives also identified the need for 1:1 time to discuss the impact of CCD with the SLP and for information about CCD to be provided at several points over time.…”
Section: Relationshipssupporting
confidence: 64%
See 1 more Smart Citation
“…The need for peer support from other families with direct experience of CCD following TBI was a strong theme to emerge from this study and reinforces positive research findings from peer mentoring programmes (49,50). Relatives also identified the need for 1:1 time to discuss the impact of CCD with the SLP and for information about CCD to be provided at several points over time.…”
Section: Relationshipssupporting
confidence: 64%
“…A recent systematic review identified that many of the TBI specific family intervention studies were limited by small sample sizes, bias on randomisation techniques and reduced fidelity (47). The effect of individual programme components, e.g., TBI education, was also difficult to discern (48) although positive findings have recently emerged for peer support, problem solving, manualised group intervention programmes and couples' therapy (49)(50)(51)(52)(53)(54)(55)(56)(57). A number of studies have also explored whether the service needs of family members may differ depending upon their relationship to the person following TBI (56)(57)(58)(59).…”
Section: Cognitive-communication Difficulties (Ccd) Resulting From Di...mentioning
confidence: 99%
“…As highlighted in the introduction to this paper, while existing research has often framed the benefits of peer support as separate and discrete (e.g. Davies & Hall, 2005;Shilling et al, 2013;Bellon et al, 2017), the framework of benefits developed here shows that there is interconnection between benefits. Broadening recognition of the continuum and multi-F I G U R E 1 Peer support benefits framework directional interaction of possible beneficial outcomes allows better precision in articulating what family members gain from peer support, which is important for thoroughly understanding their experience of it, and allows recognition that progression along a natural continuum and interaction of benefits may be possible for at least some family members.…”
Section: Resilience and Well-beingmentioning
confidence: 93%
“…Some benefits relate to agency and positive selfperception: feeling better equipped to cope with experiences of disability within the family, having higher confidence and self-esteem and being less likely to feel guilt or blame themselves for the impact of disability within their family (Solomon et al, 2001;Davies & Hall, 2005;Thompson-Janes et al, 2016). Other benefits relate to community and belonging: reduced feelings of isolation, increased awareness of the ways they are valued and increased positive sense of community by giving back to others (Solomon et al, 2001;Davies & Hall, 2005;Shilling et al, 2013;Bellon et al, 2017). Capacity building and skill development are also noted outcomes, including greater awareness of rights, both their own and those of their family member with disability, improved knowledge about how to access information about services and an increased likelihood of engaging in social or political action to achieve their rights and access to services (Solomon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While support services provide practical assistance, research also attests to the importance of peer networks. Participation in support groups can improve participants' self-confidence and empowerment (Barak et al, 2008;Bellon et al, 2017), and emotional support from those in similar circumstances to the recipient, or those with shared experience, can be more valuable than support from healthcare professionals (Thoits, 1986;Wang et al, 2015). Hu et al (2015) identified online social networks (OSNs) as important for carers, providing informational and practical resources.…”
mentioning
confidence: 99%